2015
DOI: 10.1590/1807-2577.0067
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the mental foramen using cone beam computerized tomography

Abstract: ResumoIntrodução: O conhecimento das estruturas anatômicas localizadas na região entre os forames mentuais é de importância crucial nos planejamento pré-operatórios. Objetivo: Avaliar a posição do forame mentual relacionado aos ápices dos dentes, sua distância aos bordos da mandíbula com uso da tomografia computadorizada de feixe cônico. Material e método: Foram avaliadas 100 tomografias computadorizadas de feixe cônico da mandíbula realizada num único aparelho de tomografia. Cada imagem escolhida foi avaliada… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
11
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 20 publications
4
11
1
Order By: Relevance
“…This findings correlated with the studies performed by Saito et al 4 and Pyun et al, 9 wherein Saito et al 4 found that the lingual edge was located, on average, 3.1 mm from the lingual cortex, with no statistically significant influence with age or sex had and Pyun et al, 9 who conducted a study to investigate the deviation of the buccolingual pathway from the mandibular canal and the relationship with the location of the mental foramen found a mean value of 5.60 mm of the buccolingual measurements, using computerized tomography and the most common location of MF was along the long axis of 2 nd premolar. Their results were larger than those of the present study as they measured from the center of the mandibular canal to the lingual cortex of the mandible.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…This findings correlated with the studies performed by Saito et al 4 and Pyun et al, 9 wherein Saito et al 4 found that the lingual edge was located, on average, 3.1 mm from the lingual cortex, with no statistically significant influence with age or sex had and Pyun et al, 9 who conducted a study to investigate the deviation of the buccolingual pathway from the mandibular canal and the relationship with the location of the mental foramen found a mean value of 5.60 mm of the buccolingual measurements, using computerized tomography and the most common location of MF was along the long axis of 2 nd premolar. Their results were larger than those of the present study as they measured from the center of the mandibular canal to the lingual cortex of the mandible.…”
Section: Discussionsupporting
confidence: 93%
“…It was in accordance with the studies performed by Saito et al 4 , Leila et al, 6 Haghanifar S et al 7 and Gupta S et al Saito et al 4 found about 45% of the mental foramina were located in the apex of the second premolar. Similar findings were recorded by Leila et al 6 who performed a study, using 158 CBCT images and Haghanifar S et al, 7 who evaluated 400 panoramic radiographs with regard to the location and symmetry of the mental foramina and found that in 49.2% of radiographs, MF was in line with the second premolar.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The inferior alveolar nerve bundle enters the lower jawthrough the mandibular foramen, passes along the mandibular canal and exits from the mental foramen as the mental nerve on the body of the mandible above the tubercleof the chin [3] .Determining the precise location of the mental foramen is a key factor when considering placing dental implants or when surgical proceduresare planned in the foramenregion [4] . The precise location of such foramen is also important in some dental specialties including Operative Dentistry, Periodontics, Endodontics and OrthognathicSurgery, whenever a local anesthesia procedure is to be carried out [5][6][7][8] . In adults, the mental foramen islocated on average between 13mm and 15mm above the inferior mandibular border, but in adults presenting with bone resorption, the foramen is located closer to the alveolar crest and sometimes over it [9] .One problem in determining the precise location of the mental foramen is that such a structure cannot be neither visualized nor palpated and thus, more advanced visualization techniques DOI: 10.9790/0853-1606037885 www.iosrjournals.org 79 | Page have to be used.…”
Section: Introductionmentioning
confidence: 99%